Structural and Histopathologic Changes of Calf Tibial Bones Subjected to Various Drilling Processes - Karaca, Faruk; Kom, Mustafa; Aksakal, Bunyamin (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
Bone tissue damages such as fractures, bone tissue losses, osteolysis and necrosis caused by temperature are the serious clinical concerns in orthopaedics. In order to show the effect of heat generation in bone drilling, temperatures were recorded and analysed for various drill speed, diameter, drilling force and bone densities on fresh calf tibial bones. This study revealed that high drill speeds increase the maximum temperature of the bone while high diameters and drill forces cause a decrease in the drilling temperature. SEM and histopathologic evaluations showed that high values of drill diameter and bone density caused greater damage to the bone and lowered the drill quality around the drilled site by producing rough surfaces and higher loss of osteocytes.
Çeşitli delme i?şlemlerine tabii tutulan sı?ır tibia kemiklerinin yapısal ve histopatolojik de?işimleri
Keywords: Orthopaedics; Bone drilling; Heat; SEM; Histopathology